Modelo de Aseguramiento de la calidad y Perfil de Rector Universitario: Análisis de Criterios de Calidad (Boletín de Políticas y Gestión Educativa, 2022)
Quality assurance in higher education is a worldwide trend (UNESCO, 2016), which arises as a response to a series of demands, such as: evaluating the impact of the educational offer, justifying the public and private contribution to the system, protecting students and identifying graduation profiles (Lemaitre, 2015). For this reason, some educational systems in the world have established their own quality assurance systems, highlighting within their approaches the one that understands quality assurance as a permanent process (improvement), related to internal control and self-regulation (UC Center for Public Policies, 2011).